Performance Analysis of Battery Energy Storage Systems in Renewable Power Integration - Alamsyah, Muhammad Rizky; Sothea, Dara (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The increasing penetration of renewable energy sources such as solar and wind introduces significant challenges to power system stability due to their inherent intermittency and variability. Battery Energy Storage Systems (BESS) have emerged as a key technological solution to mitigate these challenges by providing fast response, energy balancing, and ancillary services. This study aims to analyze the performance of BESS in renewable power integration through a structured synthesis of recent empirical and modeling studies. A systematic literature-based analytical approach was employed, reviewing peer-reviewed journal articles and conference proceedings published between 2021 and 2025. The analysis focuses on performance indicators including frequency regulation, voltage stability, energy efficiency, degradation, reliability, and system adequacy. The results indicate that BESS significantly improves frequency and voltage regulation, reduces renewable curtailment, enhances system adequacy, and supports higher renewable penetration levels. However, technical limitations such as battery degradation, thermal risks, and high investment costs remain critical challenges. The study concludes that while BESS is technically effective for renewable integration, its long-term sustainability depends on optimal sizing, advanced management strategies, and supportive regulatory frameworks. This paper contributes by providing a comprehensive performance-oriented synthesis that supports planners, operators, and policymakers in deploying BESS effectively.